Irregularity Indices of Dendrimer Structures Used as Molecular Disrupter in QSAR Study. (4th December 2019) - Chen, Zhihua; Virk, Abaid ur Rehman; Habib, Mustafa; Zia, Tariq Javed; Ahmed, Imran; Shi, Ce; Nazeer, Waqas
Abstract : Dendrimers are rising polymeric structures known for their flexibility in medication conveyance and high usefulness, whose properties are same biomolecules. These nanostructured macromolecules have shown potential capacities in capturing as well as conjugating the high subatomic weight hydrophilic/hydrophobic substances by host-visitor collaborations and covalent holding (prodrug approach) individually. In quantitative structure-property relationships (QSPR), topological indices are utilized to gather properties of dendrimers. Topological indices catch symmetry of dendrimer structures and give it a logical reasoning to predict properties, for instance, viscosity, boiling points, the radius of gyrations, etc. In this report, we intend to examine dendrimers through irregularity indices that are valuable in QSPR studies. We studied sixteen irregularity indices if diverse dendrimer structures.